Anxiety sensitivity and racial differences in sleep duration: Results from a national survey of adults with cardiovascular disease. (May 2017) - Alcántara, Carmela; Giorgio Cosenzo, Luciana Andrea; Fan, Weijia; Doyle, David Matthew; Shaffer, Jonathan A.
Highlights: Anxiety sensitivity was associated with increased odds of short sleep duration. Black vs. White race was associated with increased odds of short sleep duration. Blacks had higher mean anxiety sensitivity scores than non-Hispanic Whites. Anxiety sensitivity partially mediated Black-White differences in sleep duration. Abstract: Although Blacks sleep between 37 and 75 min less per night than non-Hispanic Whites, research into what drives racial differences in sleep duration is limited. We examined the association of anxiety sensitivity, a cognitive vulnerability, and race (Blacks vs. White) with short sleep duration (<7 h of sleep/night), and whether anxiety sensitivity mediated race differences in sleep duration in a nationally representative sample of adults with cardiovascular disease. Overall, 1289 adults (115 Black, 1174 White) with a self-reported physician/health professional diagnosis of ≥1 myocardial infarction completed an online survey. Weighted multivariable logistic regressions and mediation analyses with bootstrapping and case resampling were conducted. Anxiety sensitivity and Black vs. White race were associated with 4%–84% increased odds, respectively, of short sleep duration. Anxiety sensitivity mediated Black–White differences in sleep duration. Each anxiety sensitivity subscale was also a significant mediator. Implications for future intervention science to address sleep disparities are discussed.